2021
DOI: 10.1371/journal.pgen.1009432
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific H3K9me3 gain in aged somatic tissues in Caenorhabditis elegans

Abstract: Epigenetic alterations occur as organisms age, and lead to chromatin deterioration, loss of transcriptional silencing and genomic instability. Dysregulation of the epigenome has been associated with increased susceptibility to age-related disorders. In this study, we aimed to characterize the age-dependent changes of the epigenome and, in turn, to understand epigenetic processes that drive aging phenotypes. We focused on the aging-associated changes in the repressive histone marks H3K9me3 and H3K27me3 in C. el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“… 78 Interestingly, in aged somatic tissues of C. elegans , the global H3K9me3 level increases at heterochromatic regions in the distal arms of chromosomes, but decreases in euchromatic central regions of autosomes. 79 In aged Drosophila , H3K9me3 and HP1 signals on chromosomes are significantly reduced compared with those in young flies, and overexpression of HP1 extends lifespan. 80 Additionally, diminished levels of H3K9me3 and HP1 were identified in mesenchymal stem cells (MSCs) bearing pathogenic mutations of HGPS or Werner Syndrome (WS), another human disease with accelerated aging.…”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“… 78 Interestingly, in aged somatic tissues of C. elegans , the global H3K9me3 level increases at heterochromatic regions in the distal arms of chromosomes, but decreases in euchromatic central regions of autosomes. 79 In aged Drosophila , H3K9me3 and HP1 signals on chromosomes are significantly reduced compared with those in young flies, and overexpression of HP1 extends lifespan. 80 Additionally, diminished levels of H3K9me3 and HP1 were identified in mesenchymal stem cells (MSCs) bearing pathogenic mutations of HGPS or Werner Syndrome (WS), another human disease with accelerated aging.…”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“… 126 In specific regions during aging, H3K9me2 switches to H3K9me3, another repressive mark but not enriched with direct contacts with the nuclear lamina; this may reflect aging-associated changes in subnuclear location of peripheral chromatin and associate with shortened lifespan in aged C. elegans somatic tissues. 79 Interestingly, histone deacetylase or methyltransferase inhibitors alter histone modifications in ways that predominantly increase euchromatin or decrease heterochromatin. 127 These results suggest that chromatin remodeling is largely related to the level of histone post-translational modifications.…”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“…Pioneering microarray studies identified various transcription factors as important regulators of aging, including ELT-3 ( Budovskaya et al 2008 ), ELT-2 ( Zhang et al 2013 ), and PQM-1 ( Tepper et al 2013 ). Aging increases intragenic spurious transcription, cryptic transcription ( Sen et al 2015 ), the transcription of repetitive elements ( LaRocca et al 2020 ; Li et al 2021 ), and transcriptional drift ( Rangaraju et al 2015 ) in C. elegans . In addition, the reorganization of the transcription program during aging is accompanied by chromatin remodeling ( Riedel et al 2013 ), histone methylation ( Pu et al 2015 , 2018 ), and transcription elongation ( Ghazi et al 2009 ; Amrit et al 2019 ; Debès et al 2019 ).…”
mentioning
confidence: 99%
“…Similarly, maintaining lamina but disrupting chromatin attachment increased chromatin compaction in C. elegans embryos 65 . Disrupting LADs can also show localized alterations in accessibility, with recent work demonstrating Lamin B loss leads to repositioning of disease causing loci away from the nuclear periphery in post-mitotic neurones 67 and alter repressive H3K9me3 marks in C. elegans 68 . These conflicting instances, along with our data, suggest that accessibility both globally, and locally for specific loci, could be context specific, and thus our data suggests that in the context of aging, reduced accessibility could be coupled to dysfunction.…”
Section: Discussionmentioning
confidence: 99%